2021
DOI: 10.31235/osf.io/94f27
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Technology, Pedagogy & Assessment: Challenges of COVID19-Imposed E-Teaching of ESP to Saudi Female PY Students

Abstract: The Coronavirus Disease (Covid-19) triggered substantial shifts in the education systems worldwide as teaching and learning have had to shift from face-to-face to an entirely virtual model due to the closure of educational institutes. The present paper is a descriptive-analytical investigation of the challenges of the current pandemic-imposed E-teaching of English for Specific Purposes (ESP) courses to female preparatory (PY) year students at King Khalid University (KKU). It identifies teachers’ and students’ … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Teachers also stated that it was possible to co-construct (negotiate) meaning in SOLs with other students via text-chat, audio, introductory activities, visual aids, or eliciting answers slowly. Although teachers were largely confident about their ability to promote classroom interaction, future studies can explore learner perspectives as well because only few learners in Alvi et al's (2021) ER-ELT study "agreed that teachers make them participate in the interpretation and meaningmaking process" online (p. 345). There appears to be a discrepancy between teacher and learner perceptions as regards classroom interaction in SOLs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Teachers also stated that it was possible to co-construct (negotiate) meaning in SOLs with other students via text-chat, audio, introductory activities, visual aids, or eliciting answers slowly. Although teachers were largely confident about their ability to promote classroom interaction, future studies can explore learner perspectives as well because only few learners in Alvi et al's (2021) ER-ELT study "agreed that teachers make them participate in the interpretation and meaningmaking process" online (p. 345). There appears to be a discrepancy between teacher and learner perceptions as regards classroom interaction in SOLs.…”
Section: Discussionmentioning
confidence: 99%
“…The findings indicated that most teachers agreed that interaction is hindered 'when teachers lack technological skills to use the platform effectively in online classes' or 'when students are unfamiliar with the tools of the platform'. Digital illiteracy can be one reason why low or lack of interaction is observed in SOLs (Alvi et al, 2021;Hazaea et al, 2021). Teachers in this study suggested that lack of technological skills can be overcome by workshops for teachers and learners on tool use.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations